2015
DOI: 10.1155/2015/987232
|View full text |Cite
|
Sign up to set email alerts
|

Microseismic Signal Characterization and Numerical Simulation of Concrete Beam Subjected to Three-Point Bending Fracture

Abstract: To study the generation mechanism and failure mode of cracks in mass concrete, microseismic monitoring is conducted on the fracture processes of the three-point bending roller compacted concrete (RCC) beam of Guanyinyan hydropower station. The spectrum characteristics of microseismic signals in different deformation and failure stages of the concrete beam are analyzed, and the identification method of the fracture stages and crack propagation precursors of concrete beam is established. Meanwhile, the Realistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…(2015) observed that the dominant frequencies are in the low-frequency (approximately 3 kHz) and high-frequency (6–10 kHz) bands. In the present study, the sensor frequency range is 0.05–10 kHz, which is wider than that proposed by Xu et al. (2015).…”
Section: Micro-seismic Monitoringmentioning
confidence: 54%
See 2 more Smart Citations
“…(2015) observed that the dominant frequencies are in the low-frequency (approximately 3 kHz) and high-frequency (6–10 kHz) bands. In the present study, the sensor frequency range is 0.05–10 kHz, which is wider than that proposed by Xu et al. (2015).…”
Section: Micro-seismic Monitoringmentioning
confidence: 54%
“…The dominant micro-seismic signal frequencies in the plastic deformation and failure deformation stages of rock mass are in the kilohertz order (Zhuang et al, 2019). Xu et al (2015) observed that the dominant frequencies are in the low-frequency (approximately 3 kHz) and high-frequency (6-10 kHz) bands. In the present study, the sensor frequency range is 0.05-10 kHz, which is wider than that proposed by Xu et al (2015).…”
Section: Micro-seismic Monitoring Systemmentioning
confidence: 97%
See 1 more Smart Citation
“…However, these algorithms are all based on the second-order statistics and the assumption that the noises follow the Gaussian distribution. In the process of microseismic monitoring, noisy signals are non-Gaussian and their pulse characteristics are obvious (Xu et al, 2015;Jia et al, 2016). Therefore, Eq.…”
Section: The Basic Model Of Tdoamentioning
confidence: 99%
“…Since the classic article on TDOA written by Knapp and Carter was published in 1976, this problem has perpetually been a research focus in the field of international signal processing (Knapp et al, 1976). The common method of TDOA includes the generalized cross correlation method (Knapp et al, 1976;Souden et al, 2010;Jin et al, 2013), the phase spectrum estimation method (Youn et al, 1982;Qiu et al, 2012), the generalized bi-spectral estimation method (Hinich et al, 1992;Hou et al, 2013), the adaptive estimation method (Gedalyahu et al, 2010;Salvati and Canazza, 2013), the energy method based on HilbertHuang transform and so on. These methods have been widely used in many fields.…”
Section: Introductionmentioning
confidence: 99%